A universal PCR method and its application in sequence-based identification of microorganisms in dairy. (October 2018) - Zhang, Hongfa; You, Chunping
Abstract: To resolve problems with dairy product quality related to microbial contamination, it is necessary to be able to identify microorganisms in those dairy products quickly and accurately. With traditional PCR-based methods for microbial identification, specific primers need to be designed for the different microorganisms. In this study, we developed a universal PCR method with two semi-random primers to amplify microbial genomic DNA without considering the gene sequence of the test microorganism. The sequence obtained using this method was specific and could be used to identify the microorganism. The DNA sequences of known microorganisms related to dairy were amplified and identified to the species level, confirming the validity of this method. The DNA sequences of unknown common microorganisms were then amplified directly without culturing, and these microorganisms could also be identified to the species level. Compared with the common rRNA sequencing methods, this new method has high universality and resolution.